A polysaccharide synergistically thickened amino acid cleansing gel composition and method of making same
Patent Information
- Application Number
- CN202611379258.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]鉴于上述分析,本发明的目的在于提供一种多糖协同增稠的氨基酸洁面凝胶组合物及其制备方法,以解决单一多糖增稠体系黏度及稳定性不足、脂肪酰基氨基酸在终端体系中直接中和时工艺控制难度较大,以及单一氨基酸表面活性剂泡沫性能有限的问题
1.两种多糖经充分水化后共同产生增稠作用,协同增稠指数SI≈1.18(>1),复配后的增稠效果高于两种多糖分别单独使用时黏度的算术和,使组合物在保持透明凝胶状态的同时获得优于单一多糖体系的增稠性能。
Smart Images

Figure CN122998003A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of daily chemical products and cosmetic compositions, specifically to an amino acid facial cleansing gel composition with polysaccharide synergistic thickening and its preparation method. Background Technology
[0002] As a type of cleansing cosmetic, facial cleansing gels, in addition to basic cleansing ability, also need to consider foaming properties, rheological properties, storage stability, and post-use skin feel. Fatty acyl amino acid surfactants have relatively mild cleansing properties and are therefore widely used in cleansing products such as facial cleansing gels and facial washes. However, the thickening, foaming, and stability properties of amino acid surfactant systems are easily affected by factors such as the type of surfactant, the type of thickener, the pH of the system, and the electrolyte environment, thus presenting certain technical challenges in formulation design and preparation.
[0003] Existing technologies have yielded considerable research on amino acid-based facial cleansing systems. For example, CN108992364B discloses a moisturizing facial cleanser containing sodium lauroyl glutamate, which uses sodium lauroyl glutamate in combination with other surfactants, thickeners, and moisturizing components to achieve corresponding cleansing and usability performance. This type of solution can meet the basic usage requirements of facial cleansing products, but its product performance still largely depends on the combination of thickeners, surfactants, and other auxiliary components. When the amount of thickener or the system composition changes, it can easily affect the product's transparency, viscosity, spreadability, and foaming properties. Therefore, there is still room for further coordination between transparent appearance, suitable viscosity, and foaming performance.
[0004] CN114869821B discloses an amino acid facial cleanser and its preparation method, which uses multiple amino acid surfactants and adjusts the stability and rheological properties of the system through components such as carbomer and xanthan gum. This type of approach can improve the product's suspension and usability to some extent through a composite thickening system, but the compatibility between different thickening components and the matching relationship between the thickening system and the amino acid surfactants are quite complex. When using synthetic polymer thickeners such as carbomer, the degree of neutralization and the influence of electrolytes and surfactants on its thickening performance need to be further considered; while using only naturally derived colloids may result in insufficient thickening efficiency, a soft gel structure, and difficulties in simultaneously achieving transparency or long-term stability.
[0005] Furthermore, fatty acyl amino acids typically require neutralization to form corresponding salts before achieving good aqueous dispersibility and surface activity. Currently, the preparation of facial cleansers containing fatty acyl amino acids usually requires the addition of alkaline substances to the formulation system for neutralization or pH adjustment. With the gradual addition of thickeners, surfactants, and other components, the system viscosity, ionic strength, and local material concentration all change, potentially affecting the dispersion of the neutralizing component, the control of the neutralization endpoint, and the final product state. Particularly in high-viscosity systems, insufficient local dispersion of the neutralizing agent can easily cause local pH differences, placing high demands on the order of material addition, stirring conditions, and temperature control during the production process.
[0006] On the other hand, facial cleansing gels typically have a high aqueous content, thus requiring a suitable preservative system. While traditional preservatives possess relatively mature microbial control capabilities, the increasing use of naturally derived ingredients in cosmetics necessitates that preservative systems not only meet microbial stability requirements but also consider compatibility with surfactants, thickeners, and other ingredients. The ability to control bacteria and fungi may vary when some naturally derived or multifunctional preservative components are used alone, and increasing their dosage may affect the product's feel, transparency, or system stability. Therefore, achieving comprehensive microbial control at lower dosages requires further optimization.
[0007] Therefore, while existing amino acid facial cleansers have improved performance through surfactant blending, thickening system adjustments, and neutralization and preservative design, the following issues remain in practical applications: Thickening ability, transparency, and storage stability of naturally derived thickening systems are difficult to balance simultaneously; the foaming performance and gentle feel of amino acid surfactant systems still require further balancing; the neutralization process of fatty acyl amino acids is easily affected by the viscosity of the final system and the formulation environment; and the preservative system needs to consider both the control effect on different types of microorganisms and their compatibility with the overall formulation. Therefore, existing amino acid facial cleansing gels still require further improvement in areas such as the coordination of rheological properties and transparency of naturally derived thickening systems, control of the fatty acyl amino acid neutralization process, balance between foaming performance and user experience, and microbial stability. Summary of the Invention
[0008] Based on the above analysis, the purpose of this invention is to provide an amino acid facial cleansing gel composition with polysaccharide synergistic thickening and its preparation method, so as to solve the problems of insufficient viscosity and stability of single polysaccharide thickening system, difficulty in process control when fatty acyl amino acids are directly neutralized in terminal system, and limited foaming performance of single amino acid surfactant.
[0009] To solve the above-mentioned technical problems, the present invention provides the following technical solution: This invention provides an amino acid facial cleansing gel composition with polysaccharide synergistic thickening. Based on the total mass of the final formulation raw materials of the facial cleansing gel composition, the final formulation raw materials include phase A, phase B, phase C and phase D by weight percentage.
[0010] Phase A comprises 65%–80% water, 2%–5% 1,3-propanediol, 0.3%–1% crude extract of red algae, and 0.3%–0.8% xanthan gum.
[0011] Phase B comprises 3%–8% sodium lauroyl glutamate and 5%–15% lauroyl alanine arginine pre-neutralization solution.
[0012] The C phase comprises 3%–8% water, 0.2%–0.8% L-arginine, and 0.1%–0.5% sodium citrate.
[0013] The D phase comprises 0.5%–1.5% octyl glycol and 0.3%–0.8% glyceryl caprylate.
[0014] The weight ratio of the crude extract of the red algae to xanthan gum is 1:0.5 to 1:1.5; the lauroyl alanine arginine pre-neutralization solution is an intermediate prepared independently in advance before the final formulation of the facial cleansing gel composition, formed by neutralizing lauroyl alanine with L-arginine, and added to the final formulation system in the form of a pre-prepared intermediate.
[0015] The A, B, C, and D phases described in this invention are used to characterize the raw material grouping and addition stages in the preparation process of the final formulation, and do not indicate that the final cleansing gel composition forms four separate phases in a macroscopic state; the raw materials of each phase are added and mixed in the corresponding steps to form the cleansing gel composition.
[0016] The term "total mass of raw materials in the final formulation" as used in this invention refers to the total mass of each raw material used to form the final facial cleansing gel composition in steps S2 to S5. Among them, the lauroyl alanine arginine pre-neutralized liquid prepared in step S1 is used as a pre-prepared intermediate. The total mass of the raw materials in the final formulation is calculated based on the mass of the pre-neutralized liquid as a whole, without further separating each internal component and including it in the percentage of raw materials in the final formulation.
[0017] The crude extract of red algae is a complex extract obtained by water extraction of red algae, which includes red algal polysaccharides, algal proteins and minerals.
[0018] In a specific embodiment, the crude Rhodophyta algae extract used is a light yellow to white powdery raw material, with a pass rate through an 80-mesh sieve of ≥90%, a moisture content of ≤12%, a pH value of 5.0 to 10.0 for its 1% aqueous dispersion, and a transparency of ≥80%; the above appearance, particle size, moisture, pH and transparency indicators are used for raw material quality control of the crude Rhodophyta algae extract used.
[0019] In this example, the crude Rhodophyta algae extract used is a commercial powdery raw material, with an INCI name of KOUSOU EKISU (紅藻エキス); controlled according to the raw material quality standard, its lead content is ≤2.0 mg / kg, mercury content ≤1.0 mg / kg, arsenic content ≤2.0 mg / kg, total bacterial count ≤5000 CFU / g, total mold and yeast count ≤300 CFU / g; in a specifically adopted batch of raw materials, the measured pH of the 1% aqueous dispersion is about 9.0, the transparency is 81.2%, the loss on drying is 8.8%, the total bacterial count is <800 CFU / g, and the total mold and yeast count is <300 CFU / g; the detection of the above indicators is carried out in accordance with the corresponding raw material quality standards and the methods specified in the "Safety and Technical Standards for Cosmetics" (2015 Edition).
[0020] Further, the Rhodophyta polysaccharide includes at least one of κ-carrageenan type polysaccharide, ι-carrageenan type polysaccharide and λ-carrageenan type polysaccharide; the crude Rhodophyta algae extract is used in the form of a composite extract containing multiple water-soluble components, and is not required to be a single carrageenan component obtained by separation and purification.
[0021] The Rhodophyta polysaccharide and xanthan gum in the crude Rhodophyta algae extract are fully hydrated and jointly distributed in the aqueous phase, and jointly participate in the formation of the rheological state of the system; without being limited by a specific theoretical mechanism, the combination of the two polysaccharides makes the resulting system exhibit thickening properties different from those when either polysaccharide is used alone.
[0022] Preferably, the weight ratio of the crude Rhodophyta algae extract to xanthan gum is controlled to be 1:0.5 to 1:1.5; when the ratio of the two deviates excessively from the above range, the coordination relationship between the thickening effects of the two polysaccharides changes, which is not conducive to balancing the gel state and rheological properties of the composition.
[0023] The pre-neutralized lauroyl alanine arginine solution is an aqueous solution containing lauroyl alanine arginine salt formed by neutralizing lauroyl alanine with L-arginine.
[0024] The lauroyl alanine arginine pre-neutralization solution is prepared independently before the final formulation of the facial cleansing gel composition and added to the final formulation system as a pre-formulation intermediate. By separating the neutralization reaction of lauroyl alanine from the polysaccharide hydration and subsequent mixing process in the final formulation, the neutralization reaction can be carried out before a high-viscosity polysaccharide thickening system is formed, which is beneficial to the uniform dispersion and material contact of L-arginine in the neutralization system. At the same time, the pH value, active ingredient content and appearance of the pre-neutralization solution can be independently tested, and the neutralization reaction temperature and neutralization endpoint can be independently controlled.
[0025] Furthermore, the active ingredient content of the commercial raw material sodium lauroyl glutamate used is 40%; based on the dry weight of the surfactant, the mass ratio of the sodium lauroyl glutamate to the lauroyl alanine arginine salt in the pre-neutralized solution is 1:1.5 to 1:3.
[0026] The active ingredient content of the lauroyl alanine arginine pre-neutralization solution is 20%–35%, and the pH value is 6.0–6.5.
[0027] It should be noted that the content of the active ingredient is used as a quality control indicator for the lauroyl alanine arginine pre-neutralization solution, and the same quality control criteria are used to determine the content in each embodiment.
[0028] Preferably, the lauroyl alanine-arginine pre-neutralization solution is a colorless to slightly yellow transparent liquid; at 20°C, its refractive index is 1.444–1.454, and its density is 0.974–0.986 g / cm³. 3 .
[0029] In some embodiments, caprylyl glycol and glyceryl caprylate are not fed separately, but are fed using a ternary premix containing caprylyl glycol, glyceryl caprylate, and 1,3-propanediol; based on the mass of the ternary premix, the caprylyl glycol content is 47%–53%, the glyceryl caprylate content is 23%–33%, and the 1,3-propanediol content is 14%–30%; when using the premix, the corresponding amount of each active component in the final formulation is calculated based on the actual content of each active component in the premix.
[0030] In this invention, L-arginine is added in two different stages: in step S1, L-arginine is used to neutralize lauroyl alanine to obtain a pre-neutralized solution containing lauroyl alanine arginine salt; in phase C, L-arginine is used to adjust the acid-base environment of the final formulation; the L-arginine added in the two stages is measured separately.
[0031] Furthermore, the weight ratio of octyl glycol to glyceryl caprylate in phase D is 1:0.3 to 1:1.
[0032] The pH value of the facial cleansing gel composition is 5.0 to 6.5.
[0033] Furthermore, the D phase also includes 0.1%–0.5% Ashwagandha extract, 0.3%–1% yeast fermentation product extract, 0.005%–0.05% lactic acid, and 0.2%–0.8% Centella asiatica extract.
[0034] In some embodiments, the 1,3-propanediol is bio-based 1,3-propanediol derived from corn sugar fermentation, and the L-arginine is L-arginine derived from fermentation.
[0035] The term "transparent gel" as used in this specification refers to a composition that, when visually inspected at room temperature, exhibits no obvious turbidity, no suspended matter, and no visible particles, and has a gel-like appearance capable of maintaining its own shape.
[0036] Unless otherwise stated, the pH values of the facial cleansing gel compositions in this specification refer to the values measured by a pH meter at 25°C after the sample is prepared into a 10% (w / w) dilution with water; when comparing the examples and comparative examples, the sample concentration, detection temperature and detection method remain consistent.
[0037] Preparation method The present invention also provides a method for preparing the above-mentioned facial cleansing gel composition, such as... Figure 1 As shown, it includes steps S1 to S6.
[0038] Step S1: Prepare lauroyl alanine arginine pre-neutralization solution.
[0039] A pre-neutralized solution of lauroyl alanine and arginine was prepared independently in advance; step S1 was performed independently before the preparation of the terminal cleansing gel.
[0040] Mix 1,3-propanediol and water and heat to 80-85°C; add lauroyl alanine and stir continuously to fully disperse and dissolve the lauroyl alanine.
[0041] L-arginine was slowly added for neutralization, and the neutralization reaction temperature was controlled at 75-85℃. The mixture was stirred continuously during the addition of L-arginine until the system became transparent and the pH reached 6.0-6.5, thus obtaining the lauroyl alanine arginine pre-neutralized solution.
[0042] Preferably, after adding L-arginine, continue stirring for 20-30 minutes to ensure the neutralization reaction proceeds fully.
[0043] Cool the obtained pre-neutralized solution to 40-45°C, add caprylyl glycol and glyceryl caprylate, stir well and filter for later use.
[0044] The resulting pre-neutralized solution can be filtered through a 200-mesh stainless steel screen and then sealed for storage at a temperature of 20–30°C. The storage period is preferably no more than 30 days.
[0045] The obtained pre-neutralized solution was tested for pH value, active ingredient content and appearance. If it met the predetermined quality indicators, it was used as a pre-prepared intermediate.
[0046] Step S2: Prepare phase A.
[0047] Water and 1,3-propanediol were added to the reaction vessel. Crude extract of red algae and xanthan gum were gradually added while stirring. The mixture was heated to 65-70°C and stirred for 20-30 minutes to allow the two polysaccharides to fully absorb water, hydrate, swell and disperse, resulting in a uniform phase A.
[0048] The crude extracts of red algae and xanthan gum are preferably added slowly by sprinkling to reduce the possibility of rapid local water absorption and agglomeration of polysaccharide raw materials.
[0049] After thorough hydration, crude extracts of red algae and xanthan gum form a homogeneous compound thickening system.
[0050] Step S3: Add phase B.
[0051] Sodium lauroyl glutamate and the pre-neutralized lauroyl alanine arginine solution obtained in step S1 were mixed in separate containers, heated to 80-85°C and stirred until homogeneous; the obtained phase B was slowly added to phase A obtained in step S2, avoiding the introduction of a large number of air bubbles during the addition process; after phase B was added, the system temperature was maintained at 65-70°C, and the mixture was stirred at a stirring speed of 80-100 rpm for 25-35 minutes to ensure that the surfactant system and the fully hydrated complex polysaccharide system were uniformly mixed.
[0052] Step S4: Add the C phase.
[0053] Water, L-arginine, and sodium citrate were added sequentially to separate containers and stirred until transparent to obtain phase C. The obtained phase C was slowly added to the material obtained in step S3. The system temperature was maintained at 65-70°C, and stirring was continued at a stirring speed of 80-100 rpm for 25-35 minutes to ensure that phase C was fully mixed with the main system and to adjust the acid-base environment of the final system.
[0054] Step S5: Add phase D.
[0055] After cooling the material obtained in step S4 to 40-45°C, add the D-phase raw material.
[0056] When phase D includes Ashwagandha extract, yeast fermentation product extract, lactic acid, Centella asiatica extract, caprylyl glycol and glyceryl caprylate, add Ashwagandha extract, yeast fermentation product extract, lactic acid, Centella asiatica extract, caprylyl glycol and glyceryl caprylate in sequence. Stir for 3-5 minutes after each ingredient is added before adding the next ingredient.
[0057] Adding the D phase at 40–45°C can, on the one hand, prevent the D phase raw material from being heated for a long time during the hydration and dissolution stages at the aforementioned higher temperatures, and on the other hand, facilitate the uniform dispersion of the D phase raw material during the final formulation stage.
[0058] Step S6: Filter and discharge the material.
[0059] The material obtained in step S5 is filtered through a 200-mesh stainless steel screen, and the pH and appearance of the resulting composition are tested. Preferably, the pH of the resulting composition is controlled between 5.0 and 6.5, and it is sealed and packaged when it is in a transparent gel state.
[0060] Compared with the prior art, the present invention can achieve the following beneficial effects: 1. After being fully hydrated, the two polysaccharides work together to produce a thickening effect, with a synergistic thickening index SI≈1.18 (>1). The thickening effect of the compound is higher than the arithmetic sum of the viscosities of the two polysaccharides when used alone, so that the composition can achieve thickening performance superior to that of a single polysaccharide system while maintaining a transparent gel state.
[0061] 2. By independently preparing lauroyl alanine-arginine pre-neutralization solution before the preparation of the final formulation, the neutralization reaction of lauroyl alanine is separated from the hydration and mixing process of the final polysaccharide thickening system. The high-viscosity polysaccharide system has not yet formed during the neutralization stage, which is conducive to the uniform mixing of neutralization components. At the same time, the pH value, active ingredient content and appearance of the obtained pre-neutralization solution can be independently tested, and the neutralization reaction temperature and neutralization endpoint can be controlled separately.
[0062] 3. Caprylyl glycol and glyceryl caprylate form a preservative system. The two components have different microbial control focuses in the formulation environment of the cleansing gel of this invention. The combination of the two can expand the control range of bacteria and fungi, thereby obtaining a more complete microbial control effect than using either preservative component alone. Attached Figure Description
[0063] Figure 1 This is a flowchart of the preparation process of the present invention; Figure 2 The following is a histogram comparing the viscosity of Example 1, Comparative Example 2, and Comparative Example 3; Figure 3 The graph shows the accelerated stability test results for Example 1. Figure 4This is a graph showing the results of the change in the number of target microorganisms over time in the anti-corrosion challenge test of Example 1. Detailed Implementation
[0064] The present application will now be described in further detail with reference to the accompanying drawings. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.
[0065] All raw materials used in this embodiment should meet the corresponding quality requirements for cosmetic raw materials. When comparing the performance of the same set of embodiments and comparative examples, except for the explicitly changed factors under investigation, the sources of other raw materials, preparation equipment, order of addition, and testing methods should remain consistent to reduce the influence of non-understood factors on the experimental results.
[0066] In this embodiment, the percentage content of the raw materials in the final formulation is based on the total mass of the raw materials in the final formulation; the lauroyl alanine arginine pre-neutralization solution is used as a pre-prepared intermediate, and its total mass is included in the final formulation.
[0067] Example 1 This embodiment provides a preferred polysaccharide-synergistically thickened amino acid facial cleansing gel composition; based on a total mass of 100 parts of raw materials in the final formulation, the raw materials are as follows: Table 1: Table 1. Composition of the terminal formulation in Example 1
[0068] The commercial raw material of sodium lauroyl glutamate used in this embodiment is KMRLG-95 lauroyl glutamate powder, which has an active ingredient content of 40%. The 5.00 parts listed in Table 1 are the actual amount of the commercial raw material fed in. When calculating the dry mass ratio of sodium lauroyl glutamate to lauroyl alanine arginine salt, it is calculated based on its 40% active ingredient content.
[0069] The active ingredient content of the lauroyl alanine arginine pre-neutralization solution used in this embodiment is 30%.
[0070] The lauroyl alanine arginine pre-neutralization solution, by total mass of 100 parts, comprises: 43.58 parts water, 10.22 parts 1,3-propanediol, 27.67 parts lauroyl alanine, 17.75 parts L-arginine, 0.28 parts glyceryl caprylate, and 0.50 parts caprylyl glycol.
[0071] When preparing the lauroyl alanine-arginine pre-neutralized solution, 1,3-propanediol and water are added to a pre-prepared container and heated to 80-85°C while stirring. Lauroyl alanine is added in batches while stirring until the lauroyl alanine is fully dissolved.
[0072] A portion of the water from the 43.58 samples was used to pre-dissolve L-arginine, and then slowly added to the above lauroyl alanine solution. During the neutralization reaction, the temperature was controlled at 75–85°C, and the system temperature was kept below 90°C. After the L-arginine was added, stirring was continued for 20–30 minutes until the solution became transparent, and the pH value was measured to be 6.0–6.5.
[0073] The resulting solution was cooled to 40–45°C, and octyl glycol and glyceryl caprylate were added and mixed thoroughly. After filtration through a 200-mesh stainless steel sieve, lauroyl alanine arginine pre-neutralized solution was obtained.
[0074] When preparing the terminal cleansing gel, add water and 1,3-propanediol from phase A to the main reaction vessel, and slowly sprinkle in crude extract of red algae and xanthan gum while stirring. Heat to 65-70℃ and keep warm for 25 minutes to allow the two polysaccharides to fully hydrate and swell.
[0075] Mix sodium lauroyl glutamate and the above-mentioned lauroyl alanine arginine pre-neutralized solution, heat to 80-85°C, add phase A after stirring evenly, continue stirring and keep warm for 30 minutes.
[0076] Mix water, L-arginine, and sodium citrate in a separate container until transparent, then add to the main reaction vessel, continue stirring, and keep warm for 30 minutes.
[0077] Cool the system to 45°C, then add Ashwagandha extract, yeast fermentation product extract, lactic acid, Centella asiatica extract, caprylyl glycol and glyceryl caprylate in sequence. Stir each ingredient for 3-5 minutes after adding it.
[0078] After all the D-phase raw materials were added, the mixture was filtered through a 200-mesh stainless steel sieve to obtain an amino acid facial cleansing gel composition. The resulting composition was a transparent gel with no obvious turbidity, suspended matter, or visible particles.
[0079] The appearance, color, pH value, viscosity, foaming properties, skin feel, preservative properties and storage stability of the obtained composition were tested. The specific test methods and results are shown in Table 2 below.
[0080] Table 2 Performance test results of product in Example 1
[0081] As shown in Table 2, the facial cleansing gel composition obtained in this embodiment is a completely transparent gel with a pH value of 5.4. Under the foaming test conditions used, the foam volume is 180 mL, and the foam obtained is relatively fine. The human user evaluation results show that the tightness score after washing is 1.1, the change in stratum corneum moisture content is -2.8%, and the sebum retention rate is greater than 87%. At the same time, the obtained composition passed the preservative challenge test, centrifugal stability test, high temperature stability test, low temperature stability test, and microbial limit test.
[0082] Further comparisons were made of the thickening properties of different thickening systems; under the same Brookfield viscosity test conditions, the viscosities of Example 1, Comparative Example 2, and Comparative Example 3 were 12000 mPa·s, 5900 mPa·s, and 4300 mPa·s, respectively. Specific comparison results are as follows: Figure 2 As shown, the viscosity of the system composed of crude extracts of red algae and xanthan gum is significantly higher than that of the system using either polysaccharide alone.
[0083] Furthermore, a preservative challenge test was conducted on the facial cleansing gel composition obtained in Example 1. The challenge microorganisms included Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 8739, Pseudomonas aeruginosa ATCC 9027, Candida albicans ATCC 10231, and Aspergillus niger ATCC 16404. During the preservative challenge, the total number of bacterial colonies and the logarithmic reduction value of yeast and mold were detected to further evaluate the control effect of the preservative system on different types of microorganisms. The results are shown in Table 3.
[0084] Table 3 Results of Colony Count Changes in Example 1 Anti-corrosion Challenge Test
[0085] Table 3 shows that the total bacterial count at the beginning of the experiment was 8.2 × 10⁻⁶. 6 CFU / g decreased to 4.1×10 on the second day. 5 The CFU / g concentration further decreased to <10 CFU / g on day 7, with a logarithmic decrease of >5.91, and remained <10 CFU / g on days 14, 21, and 28; the total yeast and mold colony count decreased from the initial 2.4 × 10⁻⁶. 5 CFU / g gradually decreased to 1.3×10 on day 28. 3 The CFU / g logarithmic reduction value reached 2.27; combined with the antiseptic evaluation results of each target strain, Staphylococcus aureus ATCC6538, Escherichia coli ATCC 8739, Pseudomonas aeruginosa ATCC 9027, Candida albicans ATCC 10231 and Aspergillus niger ATCC16404 were all controlled to a corresponding degree.
[0086] Based on the above, the stability of the composition obtained in this embodiment under different storage conditions was further investigated. The samples were placed under accelerated storage conditions of 40°C and 75% relative humidity and under low temperature storage conditions of -5°C. The appearance of the samples was observed at a specified time, and their viscosity and pH value were measured. The specific results are shown in Table 4 below.
[0087] Table 4 Accelerated stability data from Example 1
[0088] As shown in Table 4, during the 3-month storage period at 40℃ and 75% relative humidity, the sample remained completely transparent without any obvious stratification or abnormal appearance. The pH value changed from the initial 5.40 to 5.18 after 3 months. The sample viscosity decreased slightly in the early stage of storage, and the change became more gradual after 2 months of storage. After 3 months of storage at -5℃, the sample remained completely transparent without any obvious stratification, discoloration or crystallization.
[0089] Example 1 further illustrates the changes in viscosity and pH over time during storage at 40°C and 75% relative humidity. Figure 3 From Table 4 and Figure 3 The results show that although the viscosity of the composition changes with accelerated storage time, it remains a transparent gel throughout the entire observation period, and the pH of the system remains in the weakly acidic range, indicating that the composite polysaccharide thickening system can maintain the corresponding gel state under the formulation conditions of this embodiment.
[0090] To further quantify the thickening effect of the crude extract of red algae and xanthan gum, this application defines the synergistic thickening index SI as the ratio of the apparent viscosity of the compound system to the sum of the apparent viscosities when the two polysaccharides are used alone, i.e., SI = ηcompound / (ηxanthan gum + ηred algae).
[0091] Under the same viscosity test conditions, the viscosities of Example 1, Comparative Example 2, and Comparative Example 3 were 12000 mPa·s, 5900 mPa·s, and 4300 mPa·s, respectively. Therefore, SI = 12000 / (5900+4300)≈1.18. SI is greater than 1, indicating that under the above formulation and test conditions, the thickening effect of the compound of crude extract of red algae and xanthan gum is higher than the arithmetic sum of the viscosities when the two polysaccharides are used alone.
[0092] Example 2 This embodiment has the same basic composition and preparation method as Example 1. The difference is that the crude extract of red algae is adjusted to 0.80 parts and xanthan gum is adjusted to 0.40 parts, with a weight ratio of 2:1, which is equivalent to 1:0.5. The amount of water added in phase A is also adjusted accordingly to keep the total mass of the final formula unchanged. The types and amounts of other raw materials and the operating conditions of steps S1 to S6 are the same as in Example 1.
[0093] During the preparation process, step S2 was still kept at 70℃ and stirred for 25 min to fully hydrate and swell the crude extract of red algae and xanthan gum; the resulting composition was in a completely transparent gel state; under the same viscosity test conditions as in Example 1, the viscosity of the resulting composition was 11300 mPa·s; the foam volume was 175 mL, the tightness score after washing was 1.2 points, and the anti-corrosion challenge test was passed; these results indicate that a transparent gel system can still be obtained under the above-mentioned composite polysaccharide ratio.
[0094] Example 3 This embodiment is basically the same as Embodiment 1, except that the amount of Ashwagandha extract in phase D is adjusted to 0.40 parts, the amount of yeast fermentation product extract is adjusted to 0.80 parts, and the amount of Centella asiatica extract is adjusted to 0.60 parts, and the amount of water is adjusted accordingly to keep the total mass of the final formula unchanged. The composition of the remaining raw materials and the preparation process are the same as in Embodiment 1.
[0095] The resulting composition is in a completely transparent gel state; under the same viscosity test conditions as in Example 1, the viscosity of the resulting composition is 11000 mPa·s; the foam volume is 170 mL; the tightness score after washing is 1.0; and the anti-corrosion challenge test is passed; thus, it can be seen that even when the dosage of the active ingredient is adjusted, the composition can still maintain a transparent gel state and corresponding performance.
[0096] Example 4 This embodiment is basically the same as Example 1, except that the sodium lauroyl glutamate is adjusted to 3.50 parts, the lauroyl alanine arginine pre-neutralization solution is adjusted to 12.00 parts, and the amount of water added is adjusted accordingly. The composition of other raw materials and the preparation process remain unchanged.
[0097] The resulting composition was in a completely transparent gel state; under the same viscosity test conditions as in Example 1, the viscosity of the resulting composition was 11800 mPa·s; the foam volume was 195 mL; the tightness score after washing was 1.1 points; and the anti-corrosion challenge test was passed.
[0098] Example 5 This embodiment is basically the same as Example 1, except that the L-arginine in phase C is adjusted to 0.50 parts and the water in phase C is adjusted to 4.70 parts, while the composition of other raw materials and the preparation process remain unchanged.
[0099] The resulting composition was a completely transparent gel with a pH of 5.6. Under the same viscosity test conditions as in Example 1, the viscosity of the resulting composition was 11500 mPa·s; the foam volume was 180 mL; the tightness score after washing was 1.1; and the anti-corrosion challenge test was passed. These results indicate that even with adjustments to the amount of L-arginine, the resulting composition could still maintain a weakly acidic transparent gel state.
[0100] Example 6 This embodiment is basically the same as Example 1, except that the preservative component in phase D is a ternary premix containing caprylyl glycol, glyceryl caprylate, and 1,3-propanediol. Based on the mass of the ternary premix, the caprylyl glycol content is 47%–53%, the glyceryl caprylate content is 23%–33%, and the 1,3-propanediol content is 14%–30%. The amount of premix added is calculated based on the actual content of each component. The composition of the remaining raw materials and the preparation process are the same as in Example 1.
[0101] The resulting composition was in a completely transparent gel state; under the same viscosity test conditions as in Example 1, the viscosity of the resulting composition was 11600 mPa·s; the foam volume was 180 mL; the tightness score after washing was 1.1 points; and the anti-corrosion challenge test was passed.
[0102] Comparative Example 1 This comparative example is used to compare the differences between the synthetic polymer thickening system and the composite thickening system of red algae crude extract and xanthan gum used in Example 1.
[0103] Based on the final formulation of Example 1, the crude extract of red algae and xanthan gum were removed, the thickening component in phase A was replaced with 0.30% carbomer, and 0.06% sodium hydroxide was added for carbomer neutralization. The amount of water was adjusted accordingly to 73.10%, while the types and amounts of other raw materials remained the same as in Example 1. Except for the above adjustments, the remaining preparation conditions were performed as in Example 1.
[0104] The obtained sample was able to form a completely transparent gel system and passed the anti-corrosion test, indicating that carbomer can achieve basic thickening and gel-forming effects in the cleansing formulation system.
[0105] Comparative Example 2 This comparative example is used to evaluate the rheological properties of the facial cleansing gel system when xanthan gum is used alone after the removal of crude extracts from red algae.
[0106] Based on Example 1, the crude extract of red algae was removed, the amount of xanthan gum was adjusted from 0.50% to 1.00%, and the amount of water was adjusted accordingly to 72.01%. Other components and preparation conditions remained the same as in Example 1.
[0107] The obtained sample was in a transparent gel state; it was tested under the same viscosity test conditions as in Example 1, and its viscosity was 5900 mPa·s. The gel texture was relatively soft, and the anti-corrosion challenge test was passed.
[0108] Comparing the results with those of Example 1 and Comparative Example 3, it can be seen that under the cleansing formulation of the present invention, a transparent system can be formed when only xanthan gum is used, but its thickening ability is lower than that of the system using both crude extract of red algae and xanthan gum; the viscosity comparison relationship of Example 1, Comparative Example 2 and Comparative Example 3 is as follows: Figure 2 As shown.
[0109] Comparative Example 3 This comparative example is used to evaluate the thickening and storage stability of the facial cleansing gel system when xanthan gum is removed and crude extract of red algae is used alone.
[0110] Based on Example 1, xanthan gum was removed, the amount of crude extract of red algae was adjusted from 0.50% to 1.00%, and the amount of water was adjusted accordingly to 72.01%. The composition of other raw materials and preparation conditions remained the same as in Example 1.
[0111] The viscosity of the obtained sample was 4300 mPa·s; slight stratification was observed after storage at 40℃ for one month; in the anti-corrosion challenge test, Pseudomonas aeruginosa did not meet the Grade B requirement.
[0112] Therefore, in the formulation system of this invention, although the crude extract of red algae can provide a certain thickening effect, its viscosity and high-temperature storage stability are lower than those of the system in which crude extract of red algae and xanthan gum are used together.
[0113] Comparative Example 4 This comparative example is used to compare the differences in product appearance between other natural source composite thickening systems and the red algae crude extract-xanthan gum composite thickening system of the present invention.
[0114] Based on Example 1, the crude extract of red algae and xanthan gum were removed, and 1.0% pregelatinized starch, 0.3% guar gum and 0.2% hydroxyethyl cellulose were used as thickening components. The amount of water was adjusted to 71.01%, and the composition of other raw materials remained the same as in Example 1.
[0115] The resulting sample formed a milky white, opaque gel, and did not achieve the transparent gel appearance shown in Example 1.
[0116] The results indicate that, in the cleansing formulation environment, not all naturally sourced composite thickening systems can simultaneously meet the requirements of gel formation and transparent appearance; the red algae crude extract and xanthan gum composite system used in this invention exhibits different formulation adaptability in maintaining transparency compared to the starch-based composite thickening system.
[0117] Comparative Example 5 This comparative example is used to evaluate the foaming performance when sodium lauroyl glutamate is used as the amino acid surfactant without the use of lauroyl alanine arginine pre-neutralization solution.
[0118] Based on Example 1, phase B was adjusted to 15.00% sodium lauroyl glutamate, the lauroyl alanine arginine pre-neutralization solution was removed, and the amount of water added was adjusted accordingly. The composition of the remaining raw materials and preparation conditions were the same as in Example 1.
[0119] The resulting composition was a completely transparent gel. The foam volume was 90 mL and the foam diameter was greater than 1 mm when measured under the same foaming test conditions as in Example 1. In contrast, the foam volume of Example 1 was 180 mL and the foam diameter was 0.3–0.5 mm. Therefore, under the formulation conditions used in Example 1, the foam volume and fineness of the sodium lauroyl glutamate and lauroyl alanine arginine pre-neutralization solution used together were superior to the sodium lauroyl glutamate system alone.
[0120] Comparative Example 6 This comparative example is used to compare the differences in foaming performance and skin feel of different types of surfactant systems.
[0121] Based on Example 1, phase B was replaced with 8.00% sodium lauryl sulfate and 4.00% sodium lauryl ether sulfate, and the amount of water was adjusted accordingly. The composition of the remaining raw materials was the same as in Example 1.
[0122] The resulting composition had a foam volume of 220 mL and a post-wash tightness score of 3.5. Compared to Example 1, the sulfate surfactant system had a higher foaming capacity, but its post-wash tightness score in the human sensory evaluation was significantly higher. Therefore, this comparative example is used to illustrate that different surfactant systems have different performance characteristics in terms of foam volume and post-wash skin feel.
[0123] Comparative Example 7 This comparative example is used to compare the product performance differences between the traditional synthetic thickener-preservative combination and the polysaccharide thickener-composite preservative system of the present invention.
[0124] Based on Example 1, the thickening system was replaced with 0.30% carbomer, the preservative system was replaced with 0.80% phenoxyethanol, and the crude extract of red algae was removed. Other components were adjusted accordingly based on the total amount in the final formulation.
[0125] The resulting composition is a completely transparent gel, achieving Grade A in the preservative challenge test, with a natural source index of approximately 93%. These results demonstrate that transparency and good preservative performance can be obtained using traditional synthetic thickeners and preservatives, but the raw material composition and natural source properties differ from those in Example 1.
[0126] Comparative Example 8 This comparative example is used to evaluate the control effect of octaneglycol alone on different types of target microorganisms.
[0127] Based on Example 1, the glycerol caprylate ester in phase D was removed, the amount of caprylyl glycol was adjusted to 1.50%, and the amount of water was adjusted to 73.07% accordingly. The composition of the remaining raw materials and the preparation conditions remained the same as in Example 1.
[0128] The resulting composition was subjected to an ISO 11930 corrosion resistance challenge test, and the results were as follows:
[0129] It can be seen that, under the formulation environment of this invention, when octyl glycol is used alone, it can meet the corresponding evaluation requirements for some bacteria, but its control ability against Pseudomonas aeruginosa and the tested fungi is insufficient.
[0130] Comparative Example 9 This comparative example is used to evaluate the microbial control effect of glyceryl caprylate when used alone.
[0131] Based on Example 1, octyl glycol in phase D was removed, the amount of glyceryl caprylate added was adjusted to 1.50%, and the amount of water added was adjusted to 73.51% accordingly. The composition of the remaining raw materials and the preparation process remained the same as in Example 1.
[0132] The results of the corrosion resistance challenge test are as follows:
[0133] This indicates that under the formulation conditions of this invention, glyceryl caprylate alone can meet the corresponding preservation requirements of the tested fungi, but its control effect on the three tested bacteria is insufficient.
[0134] As can be seen from Examples 1, 8 and 9, caprylyl glycol and glyceryl caprylate have different microbial control focuses in this formulation system, and the combined use of the two can achieve a more complete preservative coverage than a single component.
[0135] Comparative Example 10 This comparative example is used to compare the performance differences between the octyl glycol-glycerol octyl ester preservative system of the present invention and the commonly used phenoxyethanol preservative system.
[0136] Based on Example 1, octyl glycol and glyceryl caprylate were removed, and 0.80% phenoxyethanol was used as the preservative component, while the amount of water added was adjusted accordingly.
[0137] The resulting composition achieved a Grade A rating in the preservative challenge test, with a natural source index of approximately 99%. During the human evaluation, some subjects reported experiencing a stinging sensation. This indicates that phenoxyethanol can provide effective preservative protection for this facial cleansing system, but there are differences compared to Example 1 in terms of the source properties of the raw materials and the user experience of some subjects.
[0138] Comparative Example 11 This comparative example is used to compare the effects of different neutralizing agents and pH adjusters on the performance of the facial cleansing gel system.
[0139] Based on Example 1, L-arginine in phase C was replaced with 0.20% sodium hydroxide, and L-arginine used to neutralize lauroyl alanine in the lauroyl alanine arginine pre-neutralization solution was replaced with 4.12% sodium hydroxide. At the same time, the amount of water added was adjusted accordingly, while the composition of other raw materials and preparation conditions remained basically the same.
[0140] The resulting composition can form a completely transparent gel and passed the preservative test. Human use evaluation results showed that the comparative example had a post-wash tightness score of 1.5 points, a change in stratum corneum moisture content of -4.5%, and 12 subjects reported a slightly astringent skin feel after washing. In contrast, Example 1 had a post-wash tightness score of 1.1 points and a change in stratum corneum moisture content of -2.8%. Therefore, under the formulation and evaluation conditions adopted in this invention, the use of L-arginine for lauroyl alanine neutralization and terminal system adjustment showed a lower post-wash tightness and a smaller decrease in stratum corneum moisture content compared to the comparative example using sodium hydroxide.
[0141] To facilitate comparison of the differences in appearance, rheological properties, foaming properties, skin feel and corrosion resistance among the various embodiments and comparative examples, the relevant test results are summarized in Table 5.
[0142] Table 5 Summary of Key Performance Comparisons of Various Embodiments and Comparative Examples
[0143] As shown in Table 5, after adjusting the proportion of compound polysaccharides, the amount of active ingredients, the proportion of surfactants, the amount of L-arginine, and the feeding method of caprylyl glycol and glyceryl caprylate, the compositions obtained in Examples 1-6 all maintained a transparent gel state, with a foam volume in the range of 170-195 mL, a tightness score of 1.0-1.2 after washing, and all passed the adopted preservative challenge test. The above results indicate that when the corresponding components are adjusted within the formulation range described in this invention, the resulting facial cleansing gel compositions can still maintain relatively stable overall performance.
[0144] Regarding the thickening system, when Example 1 used a combination of crude extract of red algae and xanthan gum, the viscosity under the test conditions was 12000 mPa·s. The viscosities of Comparative Example 2, which used only xanthan gum, and Comparative Example 3, which used only crude extract of red algae, were 5900 mPa·s and 4300 mPa·s, respectively, and Comparative Example 3 showed slight stratification during high-temperature storage. Although Comparative Example 4, which used a starch-based composite thickening system, was able to form a gel, the resulting system was opaque. Therefore, under the formulation conditions of this invention, the combined use of crude extract of red algae and xanthan gum is beneficial to improving the thickening performance and storage stability of the system while maintaining the appearance of a transparent gel.
[0145] Regarding the surfactant system, in Example 1, when sodium lauroyl glutamate was combined with a pre-neutralized solution of lauroyl alanine and arginine, the foam volume was 180 mL; in Comparative Example 5, which used only sodium lauroyl glutamate, the foam volume was 90 mL, and the fineness of the foam was also reduced; although Comparative Example 6, which used a sulfate surfactant system, achieved a foam volume of 220 mL, its post-wash tightness score increased to 3.5 points. The above results indicate that the composite amino acid surfactant system used in this invention can achieve a good balance between foam performance and post-wash comfort.
[0146] Regarding the preservative system, Example 1, which uses octyl glycol and glyceryl caprylate in combination, passed the preservative challenge test, while Comparative Example 8, which uses octyl glycol alone, and Comparative Example 9, which uses glyceryl caprylate alone, failed the complete preservative challenge test. Based on the detection results of each target microorganism, it can be seen that the two preservative components have different microbial control focuses in the formulation system of this invention, and the combination of the two is beneficial to obtaining a more complete microbial control effect.
[0147] Furthermore, in Comparative Example 11, although the resulting composition was able to maintain a transparent gel state and pass the preservative test after using sodium hydroxide instead of L-arginine for neutralization and pH adjustment, its post-wash tightness score increased from 1.1 points in Example 1 to 1.5 points, and the decrease in stratum corneum moisture content also increased. This indicates that, under the formulation and evaluation conditions adopted in this invention, using L-arginine for pre-neutralization and terminal system adjustment is more conducive to taking into account the user experience after cleansing.
[0148] Combination Figure 1 As shown in the preparation process, the present invention first independently prepares lauroyl alanine arginine pre-neutralization solution, and then sequentially performs hydration of the complex polysaccharide system, addition of the amino acid surfactant system, C-phase adjustment, and low-temperature addition of the D-phase. By separating the pre-neutralization process from the final formulation preparation process, the neutralization conditions of lauroyl alanine, the hydration conditions of the complex polysaccharide, and the subsequent low-temperature feeding conditions can be controlled separately, which helps to reduce the mutual influence between different process stages.
[0149] Figure 2 The differences in rheological properties of Example 1, Comparative Example 2, and Comparative Example 3 under the same test conditions are shown. Compared with the systems using only xanthan gum or only crude extracts of red algae, the composite polysaccharide thickening system formed by combining crude extracts of red algae and xanthan gum in Example 1 exhibits higher apparent viscosity under the test conditions. Combining the results of Comparative Example 2 and Comparative Example 3, it can be seen that the combined use of crude extracts of red algae and xanthan gum under the formulation conditions of this invention is beneficial to improving the thickening performance of the system.
[0150] Figure 3 Together with Table 4, this reflects the changes in viscosity and pH value of Example 1 under accelerated storage conditions of 40°C and 75% relative humidity over storage time. During storage, the sample remained in a transparent gel state, and the pH value changed from the initial 5.40 to 5.18 after 3 months. The viscosity decreased in the early stage of storage, and the change tended to level off after 2 months of storage.
[0151] Figure 4 The results further illustrate the population trends of the five target microorganisms during the test period in the preservation challenge test of Example 1. Combined with the changes in the total colony counts of bacteria, yeast, and mold shown in Table 3, and the preservation evaluation results of each target strain shown in Table 2, it can be seen that the preservation system has corresponding control effects on different types of target microorganisms. Combined with the detection results of Example 1, Comparative Examples 8, and 9, it can be seen that the control effects on different types of microorganisms differ when using octyl glycol or glyceryl caprylate alone, while the combined use of both is beneficial for forming a more complete microbial control effect.
[0152] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A polysaccharide-synergistically thickened amino acid facial cleansing gel composition, characterized in that, Based on the total mass of the final formulation ingredients of the facial cleansing gel composition, and by weight percentage, the final formulation ingredients include: Phase A comprises 65%–80% water, 2%–5% 1,3-propanediol, 0.3%–1% crude extract of red algae, and 0.3%–0.8% xanthan gum. Phase B, wherein Phase B comprises 3%–8% sodium lauroyl glutamate and 5%–15% lauroyl alanine arginine pre-neutralization solution; Phase C comprises 3%–8% water, 0.2%–0.8% L-arginine, and 0.1%–0.5% sodium citrate; Phase D, wherein Phase D comprises 0.5%–1.5% octyl glycol and 0.3%–0.8% glyceryl caprylate; The weight ratio of the crude extract of red algae to xanthan gum is 1:0.5 to 1:1.5; the lauroyl alanine arginine pre-neutralization solution is an intermediate prepared independently in advance before the final formulation of the facial cleansing gel composition, formed by neutralizing lauroyl alanine with L-arginine, and added to the final formulation system in the form of a pre-prepared intermediate; the active ingredient content of the lauroyl alanine arginine pre-neutralization solution is 20% to 35%, and the pH value is 6.0 to 6.
5.
2. The polysaccharide-synergistically thickened amino acid facial cleansing gel composition according to claim 1, characterized in that, The crude extract of red algae is a complex extract containing red algal polysaccharides, algal proteins and minerals obtained by water extraction of red algae. The red algal polysaccharides include at least one of κ-carrageenan type polysaccharide, ι-carrageenan type polysaccharide and λ-carrageenan type polysaccharide. The crude extract of the red algae is a light yellow to white powder with a passing rate of ≥90% through an 80-mesh sieve and a moisture content of ≤12%. The pH value of the 1% aqueous dispersion system of the crude extract of the red algae is 5.0 to 10.0, and the transparency is ≥80%.
3. The polysaccharide-synergistically thickened amino acid facial cleansing gel composition according to claim 1, characterized in that, The active ingredient content of the sodium lauroyl glutamate is 40%; based on the dry weight of the surfactant, the mass ratio of the sodium lauroyl glutamate to the lauroyl alanine arginine salt in the pre-neutralized solution is 1:1.5 to 1:
3.
4. The polysaccharide-synergistically thickened amino acid facial cleansing gel composition according to claim 3, characterized in that, The lauroyl alanine-arginine pre-neutralized solution is a colorless to slightly yellow transparent liquid with a refractive index of 1.444–1.454 and a density of 0.974–0.986 g / cm³ at 20°C. 3 .
5. The polysaccharide-synergistically thickened amino acid facial cleansing gel composition according to claim 1, characterized in that, The weight ratio of caprylyl glycol to glyceryl caprylate in phase D is 1:0.3 to 1:1, and the pH value of the facial cleansing gel composition is 5.0 to 6.
5.
6. The polysaccharide-synergistically thickened amino acid facial cleansing gel composition according to claim 1, characterized in that, Phase D also includes 0.1%–0.5% Ashwagandha extract, 0.3%–1% yeast fermentation product extract, 0.005%–0.05% lactic acid, and 0.2%–0.8% Centella asiatica extract.
7. The polysaccharide-synergistically thickened amino acid facial cleansing gel composition according to claim 1, characterized in that, The 1,3-propanediol is a bio-based 1,3-propanediol derived from corn sugar fermentation, and the L-arginine is L-arginine derived from natural fermentation.
8. A method for preparing an amino acid facial cleansing gel composition with polysaccharide synergistic thickening as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Prepare lauroyl alanine arginine pre-neutralization solution independently in advance; step S1 is performed independently before the preparation of the terminal cleansing gel; mix 1,3-propanediol and water and heat to 80-85°C, add lauroyl alanine and stir until dissolved, slowly add L-arginine, control the neutralization reaction temperature at 75-85°C, stir until the solution is transparent and the pH value is 6.0-6.5 to obtain lauroyl alanine arginine pre-neutralization solution; The lauroyl alanine arginine pre-neutralized solution was cooled to 40-45°C, and octyl glycol and glyceryl caprylate were added and then filtered for later use. The pH value, active ingredient content and appearance of the obtained pre-neutralized solution were tested. If it met the predetermined quality indicators, it was used as a pre-prepared intermediate for later use. S2. Mix water and 1,3-propanediol, add crude extract of red algae and xanthan gum, heat to 65-70°C and stir for 20-30 minutes to allow the crude extract of red algae and xanthan gum to fully swell and disperse, to obtain phase A; S3. Heat the sodium lauroyl glutamate and the pre-neutralized solution of lauroyl alanine and arginine obtained in step S1 to 80-85°C and stir until dissolved. Add it to phase A obtained in step S2, stir until dissolved, and keep warm for 25-35 minutes. S4. Mix water, L-arginine and sodium citrate and stir until dissolved and transparent. Add to the material obtained in step S3, stir evenly and keep warm for 25-35 minutes, and adjust the pH value of the system. S5. Cool the material obtained in step S4 to 40-45°C, add the D phase raw material and stir evenly; S6. Filter the material obtained in step S5 to obtain the polysaccharide synergistic thickening amino acid facial cleansing gel composition.
9. The preparation method according to claim 8, characterized in that, In step S1, the active ingredient content of the obtained lauroyl alanine arginine pre-neutralized solution is 20% to 35%. The lauroyl alanine arginine pre-neutralized solution is filtered through a 200-mesh stainless steel sieve and then sealed and stored at a temperature of 20 to 30°C.
10. The preparation method according to claim 8, characterized in that, In step S5, the D-phase raw materials include ashwagandha extract, yeast fermentation product extract, lactic acid, centella asiatica extract, caprylyl glycol, and glyceryl caprylate. After cooling the material obtained in step S4 to 40-45°C, ashwagandha extract, yeast fermentation product extract, lactic acid, centella asiatica extract, caprylyl glycol, and glyceryl caprylate are added sequentially. After each raw material is added, the mixture is stirred for 3-5 minutes before adding the next raw material. In step S6, the mixture is filtered using a 200-mesh stainless steel sieve.
Citation Information
Patent Citations
A moisturizing facial cleanser containing sodium lauroyl glutamate
CN108992364B
